2015
DOI: 10.1016/j.contraception.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of bleeding patterns in women using a combined contraceptive vaginal ring or a low-dose combined oral contraceptive on a menstrually signaled regimen

Abstract: Randomized comparison of bleeding patterns in women using a combined contraceptive vaginal ring or a low-dose combined oral contraceptive on a menstrually signaled regimen Study design: Women, 66 to each group, were randomized to continuous use of a CVR (15 mcg ethinyl estradiol/150 mcg etonogestrel) or a low-dose pill (20 mcg ethinyl estradiol/100 mcg levonorgestrel) for 360 days on a menstrually signaled regimen. Bleeding/spotting days, daily use of ring or pill, was recorded. Endpoint was the total number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…A recent trial in Australia65 randomised 172 women to continuous use for a year of either a CVR or 20 μg EE/LNG COC. Women were instructed to take a 4-day break if they bled for four consecutive days.…”
Section: How Is Chc Used?mentioning
confidence: 99%
“…A recent trial in Australia65 randomised 172 women to continuous use for a year of either a CVR or 20 μg EE/LNG COC. Women were instructed to take a 4-day break if they bled for four consecutive days.…”
Section: How Is Chc Used?mentioning
confidence: 99%
“…Delay in diagnosis, difficulty accessing treatment 21 VWF levels masked by hormones, pregnancy, comorbidities 7,8 VWF assay high variability 9,10 Iron-deficiency anemia 15 Poor cognitive, social functioning, quality-of-life [21][22][23] Malposition, expulsion of intrauterine device 26 II. Current approach to management Iron supplementation [17][18][19] Tranexamic acid 24 Levonorgestrel intrauterine device 26 Combined oral contraceptive 24 VWF concentrate 24 effect by releasing hormone into the endometrial cavity but is limited by weight gain and depression in 20% of patients, and it may be expelled as a result of large clot burden. 26 VWF concentrate replaces defective or deficient VWF protein but is limited by invasiveness and cost.…”
Section: Clinical Burden Of Hmbmentioning
confidence: 99%
“…Current approach to management Iron supplementation [17][18][19] Tranexamic acid 24 Levonorgestrel intrauterine device 26 Combined oral contraceptive 24 VWF concentrate 24 effect by releasing hormone into the endometrial cavity but is limited by weight gain and depression in 20% of patients, and it may be expelled as a result of large clot burden. 26 VWF concentrate replaces defective or deficient VWF protein but is limited by invasiveness and cost. 24 A survey of hemostasis physicians regarding management of menstrual bleeding in VWD revealed that the most common first-line therapy was COCs in 70%, followed by tranexamic acid (Lysteda) in 30%, and DDAVP in 20%.…”
Section: Clinical Burden Of Hmbmentioning
confidence: 99%